A barrier diagnostic framework in process of digital transformation in higher education institutions. (30th July 2021) - Aditya, Bayu Rima; Ferdiana, Ridi; Kusumawardani, Sri Suning
Abstract : Purpose: Existing literature has reported a barrier list that could affect the implementation of digital transformation in higher education, yet the research question of how to identify barriers remained unanswered. Thus, this study intended to address this gap. Design/methodology/approach: The research design adopted a mixed-methods approach based on the problem-centered design science research (DSR) process model for the development and evaluation of framework. Findings: This study proposed a systematic framework of three sets of components: (1) the initial set of barriers; (2) the barrier rating scheme and (3) the barrier scoring matrix. The three-component of the framework is to identify and prioritize barriers to the successful implementation of digital transformation in higher education. Research limitations/implications: The evaluation of the framework was only based on an expert opinion. Practical implications: This study provided a direction to the policymakers for designing sensible strategies to increase the chances of a successful digital transformation in higher education. Originality/value: This study contributes to the knowledge body by offering a more systematic understanding of barriers to digital transformation in higher education.